Optimasi Analisis Melting Curve untuk Skrining Cepat dan Sensitif Mutasi V1016G pada Aedes aegypti Resisten Sintetik Piretroid dengan Reaksi Rantai Polimerase Spesifik Alel - Dyah Widiastuti; Agustiningsih Agustiningsih; Ihda Zuyina Ratna Sari; Tri Ramadhani (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Detection of V1016G mutation is important for identifying the mechanism of synthetic pyrethroid resistance in Aedes aegypti population. The previous method has described an allele specific polymerase chain reaction (AS-PCR) using conventional PCR to detect the mutation. Although the method has great differentiating power and reproducibility, faster and more sensitive genotyping method is essential to accurately detect the mutation. This study evaluate the used of SYBR® Green real-time PCR and melting curve analysis (MCA) to identify the V1016G mutation. The collection of homozygous 1016G, heterozygous, and wild type (1016 V) mosquitoes DNA genome was extracted using genomic DNA mini kit. The SsoAdvanced™ Universal SYBR® Green Supermix was used to identify alleles by real-time PCR followed melting curve analysis of the amplicons. Melting curve analysis produced reproducible results for the loci tested. The melting temperature was reached at 78.5 oC for homozygous 1016G mosquito and at 86 oC for wild type mosquito. Meanwhile, the heterozigous mosquito revealed two peaks of melting temperature at both 78.5 oC and 86 oC. These easily interpretable and distinguishable melting curve results were consistent with AS-PCR results obtained for the same alleles. The described MCA application for screening V1016G mutation is fast and widely accessible also could be implemented under field conditions